2011
DOI: 10.1016/j.chom.2011.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The β-Glucan Receptor Dectin-1 Activates the Integrin Mac-1 in Neutrophils via Vav Protein Signaling to Promote Candida albicans Clearance

Abstract: SUMMARY Resistance to fungal infections is attributed to engagement of host pattern-recognition receptors, notably the β-glucan receptor Dectin-1 and the integrin Mac-1, which induce phagocytosis and antifungal immunity. However, the mechanisms by which these receptors coordinate fungal clearance are unknown. We show that upon ligand binding, Dectin-1 activates Mac-1 to also recognize fungal components and this stepwise process is critical for neutrophil cytotoxic responses. Both Mac-1 activation and Dectin-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
131
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(148 citation statements)
references
References 56 publications
(85 reference statements)
13
131
1
3
Order By: Relevance
“…Recent studies have shown that dectin-1 signaling is critical for the activation of CR3 to promote the phagocytic activity of neutrophils and C. albicans clearance (39). The previous results shown in Fig.…”
Section: Il-33 Priming Increases the Phagocytic Activity Of Neutrophimentioning
confidence: 75%
See 1 more Smart Citation
“…Recent studies have shown that dectin-1 signaling is critical for the activation of CR3 to promote the phagocytic activity of neutrophils and C. albicans clearance (39). The previous results shown in Fig.…”
Section: Il-33 Priming Increases the Phagocytic Activity Of Neutrophimentioning
confidence: 75%
“…TLRs and dectin-1 were previously reported to be necessary for protection from C. albicans infection (15)(16)(17)(18)(39)(40)(41). Collaborative recognition of distinct microbial components by TLRs and dectin-1 synergistically induced the production of proinflammatory cytokines (42,43).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, IL-33 was shown to enforce TLR and Dectin-1 signaling to upregulate complement receptor 3 (CR3) in neutrophils and increase their phagocytic activity (13,14), as well as to increase the Dectin-1-induced activation of Mac-1, a component of CR3 (20). IL-33-induced CR3 activation also results in the production of high levels of reactive oxygen species and fungicidal activity in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…These data can be reconciled if the major role of dectin-1/CARD9 is to modulate NADPH oxidase and fungal killing via soluble mediators, rather than by cell-intrinsic activation. β2 integrins and TLR signaling can collaborate with dectin-1 to mount macrophage inflammatory responses to H. capsulatum and other fungi (44,45).…”
Section: Introductionmentioning
confidence: 99%